Fabricación de un prototipo de una máquina lanzadora de balones de voleibol para entrenamientos en prácticas deportivas en la Fundación Universidad de América (2021)
Based on the project received from the university entitled "Design of a volleyball throwing machine for training in sports practices at the University of America Foundation", together with drawings and supporting documents, a design analysis diagnosis is carried out, in which the stability and weight factors were evaluated, passing through the five subsystems that compose it and the cost analysis, in which the revised arithmetic summations of the costs found in the document were made using the March 2020 CPI to make a comparison with the other machines found in the market.